Recent Developments on Catalyst‐Free, Visible‐Light‐Triggered Synthesis of Heterocyclic Scaffolds and Their Mechanistic Study. Issue 36 (23rd September 2021) - Goswami, Munmee; Dutta, Arup; Paul, Pooja; Nongkhlaw, Rishanlang
Abstract: In recent years, visible‐light promoted reactions have become a powerful tool for organic synthesis by activating small molecules. This review presents an overview of the catalyst‐free synthesis of heterocyclic compounds with one or more than one heteroatoms under visible‐light irradiation in various solvents or solvent‐free conditions reported from 2013 on. Abstract : This perspective presents an overview of a catalyst‐free synthesis of heterocyclic compounds with one or more than one heteroatoms under visible‐light initiated in various environmentally benign conditions reported from 2013 onwards. Clean source of energy as well as the absence of catalyst makes it even more environmentally safe, which will be the beginning of a great progress in organic transformations in a little while.